2023
DOI: 10.1371/journal.ppat.1011493
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 is indispensable for survival of pneumococcal pneumonia in mice

Lena Ostermann,
Benjamin Seeliger,
Sascha David
et al.

Abstract: S100A8/A9 has important immunomodulatory roles in antibacterial defense, but its relevance in focal pneumonia caused by Streptococcus pneumoniae (S. pneumoniae) is understudied. We show that S100A9 was significantly increased in BAL fluids of patients with bacterial but not viral pneumonia and correlated with procalcitonin and sequential organ failure assessment scores. Mice deficient in S100A9 exhibited drastically elevated Zn2+ levels in lungs, which led to bacterial outgrowth and significantly reduced survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Notably, a significant release of CP has been observed during the course of pneumococcal infections ( Raquil et al, 2008 ). In an infection model involving mice lacking S100A9, it was observed that pneumococcal pneumonia worsened ( Ostermann et al, 2023 ). The sequestration of Mn 2+ by CP plays a crucial role in the defense against infection and is a vital component of the innate immune response to bacterial pathogens.…”
Section: Manganese Transport Systemsmentioning
confidence: 99%
“…Notably, a significant release of CP has been observed during the course of pneumococcal infections ( Raquil et al, 2008 ). In an infection model involving mice lacking S100A9, it was observed that pneumococcal pneumonia worsened ( Ostermann et al, 2023 ). The sequestration of Mn 2+ by CP plays a crucial role in the defense against infection and is a vital component of the innate immune response to bacterial pathogens.…”
Section: Manganese Transport Systemsmentioning
confidence: 99%
“…Calprotectin could modulate cyclooxygenase activity to regulate the expression of prostaglandin analogs, promoting the adhesion of phagocytes to the vascular endothelium and thrombi formation 13,14 . Moreover, it has potent antimicrobial effects against various bacterial and fungal pathogens 15 . As an acute phase reactant, the expression level of calprotectin is often increased following infection, trauma, and inflammatory diseases such as rheumatoid arthritis, ankylosing spondylitis, and inflammatory bowel disease, serving as a biomarker to help with the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Moreover, it has potent antimicrobial effects against various bacterial and fungal pathogens. 15 As an acute phase reactant, the expression level of calprotectin is often increased following infection, trauma, and inflammatory diseases such as rheumatoid arthritis, ankylosing spondylitis, and inflammatory bowel disease, serving as a biomarker to help with the diagnosis. In particular, fecal calprotectin has become one of the most important indicators for monitoring inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%